Peculiarities of the neck growth process during initial stage of spark-plasma, microwave and conventional sintering of WC spheres - Demirskyi, Dmytro (2013)
This work involves an investigation of the neck growth kinetics of free-packed spherical shaped binderless tungsten carbide particles during microwave and spark-plasma sintering. The application of a classical sphere to sphere approach showed the possibility of identifying the main diffusion mechanisms operating during the initial stage of microwave sintering of tungsten carbide powder. An anomalous neck growth rate in the initial period during microwave and spark-plasma sintering processes, up to 100 times faster in comparison to conventional sintering, was also revealed. Volume diffusion was enhanced by a small amount of a liquid phase, and surface diffusion was proposed as the primary mass transport mechanism for microwave sintering. The simulation operation of grain-boundary diffusion and power law creep was responsible for neck growth during spark-plasma sintering.